I have a problem, solve for x.

ln(x+2)-2ln(3)=0 ln(x+2)-2ln3=0

So I guess 2ln(3)=2ln

But first I did this because I didn't notice the second equation.

ln(x+2)=2ln(3)

[e^(2ln(3)]=x+2

x=[e^2ln(3)]-2

What do you think?

Printable View

- Aug 23rd 2011, 10:41 AMStudentMCCSwhat's the difference between 2ln3 and 2ln(3)
I have a problem, solve for x.

ln(x+2)-2ln(3)=0 ln(x+2)-2ln3=0

So I guess 2ln(3)=2ln

But first I did this because I didn't notice the second equation.

ln(x+2)=2ln(3)

[e^(2ln(3)]=x+2

x=[e^2ln(3)]-2

What do you think? - Aug 23rd 2011, 10:50 AMSironRe: what's the difference between 2ln3 and 2ln(3)
Your solution to solve is fine, but you can simplify it this way:

and therefore

Also notice:

But this statement:

doesn't make sense ... the two given equations are totally equal.